Rancang Bangun dan Uji Performansi Alat Penyiang Gulma pada Tanaman Kacang Tanah - Muhammad Dhafir; Andriani Lubis; Cut Zakiyya (Rona Teknik Pertanian, 2012)
Weeds were plants whose presence was undesirable because it lowered the yield of agricultural land that could be achieved by the production plant. Weeding the groundnut crop had been done conventionally, weeding method had many drawbacks. The purpose of this research was to design, fabricate and per-formance test of the weed clean device on peanut plants. The results showed that the dimensions of the weed clean device was 1332 mm long, connecting rods were made of pipe with a diameter of I inch, wide handlebars 732 mm diameter, wheel steering handlebars handheld was 48 mm, wheelbase was 150 mm steel, blade was made of steel plate 2 mm with a length of 250 mm and a width of 20 mm. The strength and durability of the weed clean device were met because the stress permis (131 MPa) was greater than the stress occurred (16.9 Mpa). From the obtained performance test of weed clean device capacity was 16 hours /ha, better than weeding manually, 90 hours /ha.